Analisis Pengendalian Persediaan Bahan Baku Tepung Terigu Dengan Metode Economic Order Quantity Pada Pabrik Roti Sdap Jaya di Kota Manado - Rampun, Kristina; Kaunang, Rine; Loho, Agnes Estephina (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2023)
This study aims to determine the procurement of wheat flour raw material inventory at the Sdap Jaya Bread Factory is optimal or not optimal. This research was conducted for 4 months, from April to July 2023. The data used in this study are primary data and secondary data. Primary data is obtained through leadership interviews, to the head of production and the head of administration, while secondary data is obtained from data that has been arranged in the form of written documents from the company, literature and the internet. Data is processed using the EOQ method. The results showed that the procurement of wheat flour raw material inventory at the Sdap Jaya Bread Factory was not optimal because the inventory was greater than the EOQ method. The inventory of raw materials at the Sedap Jaya Bread Factory is 2500 kg to 3000 kg of raw materials, while to avoid excess inventory of raw materials the order that must be made according to the EOQ method is 1,738 kg with 6 orders.